Surface modification of nitrogen-doped carbon quantum dots for enhanced functionalities - Pham, Van Duong; Le , Anh Thi; Do, Minh Hieu; Le Thi, Thu Huong; Nguyen, Duc Toan; Pham, Hong Minh; Nguyen, Trong Tuyen; Nguyen, Dinh Lam; Nguyen, Minh Hoa; Nguyen, Thanh Binh (Communications in Physics, 2024)
A facile and controllable one-step atmospheric pressure microplasma method was employed to synthesize nitrogen-doped carbon quantum dots (N-CQDs) with tunable optical properties. The N-CQDs were characterized using Fourier transform infrared spectroscopy, high-resolution transmission electron microscopy, UV‒Vis absorption spectroscopy, and photoluminescence spectroscopy. HRTEM revealed uniformly distributed spherical nanoparticles with a graphite-like structure. FTIR confirmed effective nitrogen doping, enhancing chemical stability. UV‒Vis spectroscopy revealed redshifted absorption peaks, indicating improved electronic interactions and a reduced bandgap (4.05 eV) compared to those of undoped CQDs (4.18 eV). PL analysis revealed excitation-dependent emission and a significantly higher photoluminescence quantum yield (PLQY) of 33.09%. These results suggest that N-CQDs hold promise for applications in optoelectronics and bioimaging, providing a foundation for further optimization in future studies.